A influência de fatores psicossociais protetores na incidência de dor dentária em crianças: um estudo longitudinal - Mariana Guimarães Jorge de Alvarenga (2021)
The perception of dental pain results from a complex relationship among biological, behavioural and psychosocial factors. The present study investigated the association between protective psychosocial factors and the incidence of dental pain in the last six months in 12-year-old children living in Manaus (AM). A prospective school-based cohort study was conducted with 210 12-year-old students enrolled in public schools in the eastern zone of Manaus (AM) who were followed up for 2 years. Validated questionnaires were used to assess protective psychosocial factors, including sense of coherence (SOC), social support, and self-esteem at baseline and after 2 years. Multivariate multilevel Poisson regression was used to estimate the relative risk (RR) and 95% confidence interval (95% CI) between the change in psychosocial factor scores and dental pain incidence, adjusted for psychosocial factor scores at baseline, dental health plan, frequency of tooth brushing, and dental caries. Mean SOC and social support scores reduced significantly between baseline and 2-year follow-up. The incidence of dental pain at the 2-year follow-up was 28.6%. The risk of dental pain was 14% higher for every 10 points in change in SOC score (RR = 1.14, 95%CI = 1.02 - 1.20), and 6% higher for every 10 points in change in social support score (RR = 1.06, 95%CI = 1.01 - 1.11). Change in self-esteem was not associated with risk of dental pain. The change in SOC and social support over the 2-year period influenced the incidence of dental pain in children.